2014
DOI: 10.1016/j.kjms.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome and risk of coronary artery disease in patients with chronic schizophrenia or schizoaffective disorder in a chronic mental institute

Abstract: The prevalence rate of metabolic syndrome (MS) and coronary artery disease (CAD) has been found to be high in patients with chronic schizophrenia. Current evidence shows that CAD is underdiagnosed in this group. Our study evaluated the prevalence of MS and the risk of CAD in patients with chronic schizophrenia in a chronic care mental hospital in southern Taiwan. We included all patients with the diagnosis of schizophrenia or schizoaffective disorder. We collected all laboratory, physical examination, psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…[2426] The finding that patients with schizophrenia would have higher 10-year risk of coronary heart disease is also similar to earlier report by Tseng et al [26] That finding is not surprising given the criteria of metabolic syndrome and Framingham points have overlapping parameters.…”
Section: Discussionsupporting
confidence: 83%
“…[2426] The finding that patients with schizophrenia would have higher 10-year risk of coronary heart disease is also similar to earlier report by Tseng et al [26] That finding is not surprising given the criteria of metabolic syndrome and Framingham points have overlapping parameters.…”
Section: Discussionsupporting
confidence: 83%
“…Thirty studies were included for meta-analyses (Arango et al, 2008;Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Centorrino et al, 2012;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Elgamal et al, 2012;Gladigau et al, 2014;Gulec Oyekcin, 2009;Hatata et al, 2009;Holt et al, 2010;John et al, 2009;Keenan et al, 2013;Khatana et al, 2011;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;MedeirosFerreira et al, 2013;Miller et al, 2013;Morgan et al, 2014;Pantusa et al, 2010;Risselada et al, 2012;Roshdy, 2011;Schorr et al, 2009;Steylen et al, 2009;Tseng et al, 2014;van Winkel et al, 2008;Wysokinski et al, 2012), using also unpublished data provided by corresponding authors (Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Gladigau et al, 2014;Keenan et al, 2013;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;<...>…”
Section: Study Selectionmentioning
confidence: 99%
“…The majority of studies (70%) were published over the last five years (Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Centorrino et al, 2012;Correll et al, 2014;Curtis et al, 2011;Elgamal et al, 2012;Gladigau et al, 2014;Holt et al, 2010;Keenan et al, 2013;Khatana et al, 2011;Kuzman et al, 2011;Lin et al, 2012;Medeiros-Ferreira et al, 2013;Miller et al, 2013;Morgan et al, 2014;Pantusa et al, 2010;Risselada et al, 2012;Roshdy, 2011;Tseng et al, 2014;Wysokinski et al, 2012), with the oldest published in 2007 (Mackin et al, 2007). All manuscripts but four e written in Dutch (Steylen et al, 2009), Italian (Pantusa et al, 2010), Spanish (Medeiros-Ferreira et al, 2013), and Turkish languages (Gulec Oyekcin, 2009), respectively e were in English.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that patients that take antipsychotics have a higher rate of incidence of diabetes mellitus and metabolic syndrome, which may be a result of the medication together with a maladaptive lifestyle [27]. It is estimated that approximately 50% of patients treated with high-potency first-generation antipsychotics (such as haloperidol) develop acute extrapyramidal symptom within the first several days of treatment [28].…”
Section: Discussionmentioning
confidence: 99%